PENGARUH KONSELING TERHADAP PENGETAHUAN DAN SIKAP PEMBERIAN MP-ASI - Margareta Fatimah Azzahra; Lailatul Muniroh (Universitas Airlangga, 2015)
ABSTRACTGrowth failure process started since the child was still in the womb. The success of growth process is determined by feeding practices. A total of 59% of Indonesian children aged 6-23 months were given food that inappropriate with the recommendations of timing, frequency, and quality. The lack of proper feeding can be reduced by providing intervention in the form of counseling to mothers. The aim of the study was to analyze the growth and feeding counseling towards knowledge and attitudes about feeding in the area of Brambang Public Health Center, Jombang district. The study design was quasi-experimental. Samples were children aged 6-24 months with malnutrition and over nutrition. Respondents were 12 mothers of malnutrition and overnutrition children in each group. The control group was given a leaflet about eating guideline for children, health care “KMS”, and nutrition-conscious family “Kadarzi”, whereas the intervention group was given leaflet and growth-feeding counseling. The counseling was given once a month for 15-20 minutes over three months. Wilcoxon Sign Rank test was used to analyze before-after differences in knowledge and attitudes. The result showed that there was a difference in the level of knowledge in intervention group (p=0,005) and control group (p=0,0250). There was also a difference of attitude in intervention group before-after intervention (p=0,014) but not in the control group (p=0,317). The growth and feeding counseling could increase the knowledge and attitude of mothers about nutrition. The counseling should be given regularly and further effort to assess others factors beyond nutrition is needed for more effective results.Keywords: attitude, counseling, knowledge, weaning food